Training effects on muscle glucose transport during exercise - Richter, E. A.; Kristiansen, S.; Wojtaszewski, J.; Daugaard, J. R.; Asp, S.; Hespel, P.; Kiens, B. (Advances in Experimental Medicine and Biology, 1998)
Muscle glucose uptake is increased during exercise compared to rest. In general, muscle glucose uptake increases with increasing exercise intensity and duration. Whereas the arterio-venous concentration difference only increases 2-4-fold during exercise compared with rest the increase in muscle perfusion in 10-20 times and therefore quantitatively very important. During exercise the surface membrane glucose transport capacity increases in skeletal muscle primarily due to an increase in surface membrane GLUT4 protein content. Endurance training decreases muscle glucose uptake during exercise at a given absolute submaximal work-load despite a large increase in muscle GLUT4 protein content. We have shown that this decrease in glucose uptake at least in part is due to a blunted exercise-induced increase in sarcolemmal glucose transport capacity secondary to a blunted increase in sarcolemmal GLUT4 transporter number. Thus, endurance training leads to a marked reduction of the fraction of muscle GLUT4 that is translocated during a given submaximal exercise bout. Whether this is true also during exercise at higher intensities remains to be seen.